The Role Of Ibragim Muminov In The Creation Of The Uzbek Soviet Encyclopedia (Eurasian Journal of History, Geography and Economics, 2025)
In this article, the incomparable merits of Ibrahim Muminov in the science and culture of the Uzbek people, in particular, his role in the creation of the first Uzbek scientific encyclopedia, are analyzed. This large-scale scientific project, which began in the 60s of the 20th century, marked the beginning of a new stage in the history of science in Uzbekistan. The article reveals the process of forming the Uzbek Soviet Encyclopedia, the activities of the editorial staff, and bold efforts to illuminate national values, despite political and ideological obstacles. Muminov's scientific and leadership skills, his discipline, and his role in educating young personnel were also highlighted. The study recognizes the personality of Ibrahim Muminov as the founder of the Uzbek National Encyclopedia